Modeling as Craft - Fishwick, Paul (36th Annual Simulation Symposium, 2003)
Toy boats, automobiles, and planesare models that entertain and delight us inchildhood. As we grow, we might availourselves of more advanced models that aretruer to life--more real and engaging.Interactive computer games provide evengreater flexibility, while lacking in tactilefeedback and the sort of physical immersionwe expect from every day experience. Modelsthat are used in simulation for buildingsoftware and dynamic systems can be equallyas immersive, with a variety of aestheticfeatures. For example, a factory floor modelcan achieve high degrees of realism using 2Dand 3D visualization.The factory floor, like the model plane, isiconic in representation. It is a scale model.But what of the more mathematical models,including software? The structures in thesemodels, unlike with the iconic nature of scalemodeling, employ symbolic relations whereone object refers to another withoutnecessarily resembling it. We discuss aresearch project, with examples, to show thatone can retain the abstraction and rigorexpected from mathematical structure, whilesimultaneously achieving the benefits of thesort of aesthetics, styles, and engagement thatwe experience with physical models andcomputer games.